Simulation-based review of classical, heuristic, and metaheuristic path planning algorithms - Kenneth Christopher Ugwoke; Nwojo Agwu Nnanna; Saleh El-Yakub Abdullahi (Scientific Reports)
Abstract Path planning is the process by which an autonomous robot obtains information about its environment and chooses the best route from the start point to the target destination while avoiding obstacles. It is vital to the success of robot operation as it provides autonomous maneuverability within the environment, ensuring a collision-free and optimum path that guarantees efficient movement. This paper introduces and categorizes several notable path-planning algorithms used in robotics operations. We delve into their basic principles, key features, challenges, and real-world applications. Additionally, we provided a simulated comparison result of the notable path-planning algorithms. Finally, we analyze the outcomes, give a concise conclusion, and forecast the future trends in path planning techniques.